The Influence of Employee Income Supplement (TPP) and Leadership on Employee Performance with Work Motivation as a Moderating Variable in the Scope of the Secretariat of the Regional People's Representative Council (DPRD) of Kerinci Regency - Bonivia, Trevie Della; Sunarta, Sunarta; Sarji, Sarji (Riviera Publishing, 2025)
This study aims to determine, understand, and test the extent to which Employee Income Supplement (TPP) and Leadership affect Employee Performance with Work Motivation as a moderating variable within the Secretariat of the Regional People's Representative Council (DPRD) of Kerinci Regency. The respondents were all Civil Servants (ASN). Data were analyzed using statistical methods with SEM-PLS analysis techniques, which showed that TPP did not have a significant direct effect on Employee Performance (p>0.05), while Leadership and Work Motivation had a significant direct effect on Employee Performance (p<0.05). TPP also did not have a direct effect on Work Motivation, while Leadership had a direct effect on Work Motivation. Furthermore, the test of the indirect effect of TPP moderated by Work Motivation on Employee Performance showed no significant effect. However, Leadership had a significant effect on Employee Performance when moderated by Work Motivation. These findings are expected to serve as a basis for relevant parties to re-evaluate important components that influence the improvement of employee performance quality to achieve optimal organizational performance. It is also hoped that future researchers will continue to develop this study by considering variables related to employee welfare..